Transformasi Akuntansi Syariah dalam Lembaga Zakat dan Koperasi di Era Digitalisasi Keuangan Islam - Nurul Awalia; Roslindah; Masyhuri (Yayasan Darussalam Patalassang, 2025)
The era of Islamic finance digitalization has brought significant transformation in sharia accounting practices, particularly in zakat institutions and sharia cooperatives. This article analyzes the paradigm shift in sharia accounting that occurs with the adoption of digital technology in Islamic finance management. This research employs qualitative descriptive analysis method with literature review approach to understand the implementation of sharia accounting in the digitalization context. The research findings indicate that digital transformation has enhanced transparency, accountability, and efficiency in zakat fund management and sharia cooperatives through the implementation of systems such as SIMZAT and integrated digital platforms. Blockchain technology, artificial intelligence, and big data analytics provide opportunities to improve sharia compliance and real-time monitoring. However, challenges remain regarding system standardization, incomplete regulations, limited competent human resources, and high implementation costs. The practical implications of this research include the need for developing a sharia accounting framework that is adaptive to digital technology, comprehensive technical standardization, human resource capacity building through training and certification programs, and regulatory development that supports sharia accounting digitalization. This research contributes to the development of digital sharia accounting theory and provides practical guidance for stakeholders in implementing digital transformation that complies with sharia principles. The proposed framework integrates five main components: sharia principles as foundation, digital technology as enabler, accounting standards as guidelines, human resources as operators, and regulations as legal framework.